KEPATUHAN WAJIB PAJAK: PENGARUH TAX KNOWLEDGE DAN MEDIASI PERSEPSI KEADILAN PAJAK - Priyastiwi Priyastiwi; Mia Candra Dewi; Agus Eko Sutriyono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study empirically examines the effect of tax knowledge and perceptions of tax justice on taxpayer compliance. The type of research used in this study is quantitative with data collection techniques using a questionnaire. The sample in this study were individual taxpayers registered at KPP Pratama Bantul. The number of samples used was 100 respondents with a convenience sampling technique. Data analysis techniques using multiple linear regression analysis and path analysis. The results showed that tax knowledge and perceptions of tax justice had an effect on taxpayer compliance. In addition, it was found that tax knowledge through perceptions of tax justice has a significant effect on taxpayer compliance.